2017
DOI: 10.1103/physrevb.95.064412
|View full text |Cite|
|
Sign up to set email alerts
|

Spin Hall torques generated by rare-earth thin films

Abstract: We report an initial experimental survey of spin-Hall torques generated by the rare-earth metals Gd, Dy, Ho, and Lu, along with comparisons to first-principles calculations of their spin Hall conductivities. Using spin torque ferromagnetic resonance (ST-FMR) measurements and DC-biased ST-FMR, we estimate lower bounds for the spin-Hall torque ratio, ξSH, of ≈ 0.04 for Gd, ≈ 0.05 for Dy, ≈ 0.14 for Ho, and ≈ 0.014 for Lu. The variations among these elements are qualitatively consistent with results from first pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 57 publications
1
37
0
1
Order By: Relevance
“…This rectified voltage gives information on the physical parameters of the magnetic material as well as on the nature of the torques that drive the excitation. In the context of an in-plane system with AMR driven by SOTs, the mixing voltage reads Reynolds et al, 2017)…”
Section: Spin-torque Ferromagnetic Resonancementioning
confidence: 99%
“…This rectified voltage gives information on the physical parameters of the magnetic material as well as on the nature of the torques that drive the excitation. In the context of an in-plane system with AMR driven by SOTs, the mixing voltage reads Reynolds et al, 2017)…”
Section: Spin-torque Ferromagnetic Resonancementioning
confidence: 99%
“…Our results suggest that f -d interaction is a capable instrument to finely tune the group velocities of itinerant states. The new point here is the strong spin-orbit coupling which makes these states highly spin-polarized and therefore moves these phenomena potentially into the field of interest for spintronics [26,27].…”
Section: -3mentioning
confidence: 99%
“…For instance, dimensional tuning of quantum criticality in heavy-fermion systems can be achieved by suppressing the magnetic order and enhancing the effective electron mass in 2D heavy-fermion materials as compared to their 3D analogues [22]. Thus low-dimensional materials combining strong electron correlations with strong SOC are rather promising candidates for revealing new properties that can potentially provide novel [23] functionalities for technological applications, for example, in spintronic devices based on the spin-Hall effect in Kondo materials [24][25][26][27] or in noncentrosymmetric superconductors [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing h eff SH with the Tb concentration might indicate an additional contribution from the Tb atoms which have a large orbital angular momentum, and recent reports have shown that the RE atoms give rise to SOT in RE/FM heterostructures. 37,38 Although our films are alloys, it is reported that a segregation in the Tb composition, which is pronounced for low thickness, can occur and result in a relatively Tb-rich region at the top of the magnetic layer. 39,40 Since the sign of the spin Hall angle of RE is found to be positive, 37 the spin currents from the bottom W and relatively rich Tb region at the top can be additive, thereby enhancing h eff SH as the Tb concentration increases.…”
mentioning
confidence: 91%
“…37,38 Although our films are alloys, it is reported that a segregation in the Tb composition, which is pronounced for low thickness, can occur and result in a relatively Tb-rich region at the top of the magnetic layer. 39,40 Since the sign of the spin Hall angle of RE is found to be positive, 37 the spin currents from the bottom W and relatively rich Tb region at the top can be additive, thereby enhancing h eff SH as the Tb concentration increases. Alternatively, this can be ascribed to the increase in transparency of the W/CoTb interface due to the increasing Tb composition, which may alter the interface properties, such as the spin-mixing conductance and hence h eff SH .…”
mentioning
confidence: 91%